Ranging behavior of long-tailed macaques (Macaca fascicularis) at the entrance of Kuala Selangor Nature Park - Kamarul, H.; Ahmad, I.; Badrul-Munir, M. Z; Syaizwan, Z.; Aainaa, A. (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study reported the ranging behavior of a group of long-tailed macaques (Macaca fascicularis) that inhabit the area near Kuala Selangor Nature Park, Selangor, Malaysia. The data on the ranging behavior were collected daily through scan sampling from February to December 2011 on all significant individuals in the focus group. Observations were focusing on the moving distance and usage of canopy level by the study group in the exploiting habitat. They often travelled in the range between 100 and 600 m per day, and the ranging patterns were influenced by the food distribution, sleeping site, predation and territorial factors. The study group seems to use areas that are close to human settlements because of the availability and high distribution of food. The study group does not seem to move far from their home range because they will be returning to the trees along the roadside to sleep. Avoiding predators and territorial factor are the main reasons why they are using the same sleeping sites. The most frequent forest canopy strata used by the study group are the ground level (36.78%), followed by the lower canopy (35.46%), middle canopy (17.93%), upper canopy (7.74%), and the lowest is emergent (2%). Overall, ranging behavior of the study group is not only influenced by food distribution but also by other factors such as avoiding predators and territorial possession at the studied area.